Two-dimensional nanosheets of tungsten vanadate (WV2O7) obtained by assembling nanorods on graphene as a supercapacitor electrode - Lee, Ilbok; Jeong, Gyoung Hwa; Lim, Jaewoong; Kim, Sang Wook; Yoon, Songhun (Journal of Alloys and Compounds, 2018)
By cumulative assembly of tungsten vanadate (WV2O7) nanorods, novel two-dimensional (2D) nanosheets of interwoven tungsten vanadate were hydrothermally formed on graphene. When as-prepared material was applied into a supercapacitor electrode using H2SO4 electrolyte, it was clarified that charging process was based on the pseudocapacitive reaction and the average specific capacitance was 346.4 F g−1 with a high differential capacitance of 1211.4 F g-1 at −0.1 V. Furthermore, an outstanding improvement of charge retention during cyclic voltammetry was observed (68% @ scan rate 100 mV s−1) while electrode loading was as high as 5 mg cm−2, which was practically significant since the electrode fabrication was based on conventional slurry mixing process. From Ragone plot, it was revealed that the maximum energy density was as large as 27.8 Wh kg−1 at 950 W kg−1, and the power density was excellent (23.8 kW kg-1 at 16.2 Wh kg−1). The high energy and power capability were attributed to the optimized 2D assembly of WV2O7 nanorods with the easy availability of the electrolyte on the high-conductivity graphene layer.
Keywords: Conventional slurries; Differential capacitance; Electrode fabrication; High conductivity; Specific capacitance; Supercapacitor electrodes; Two Dimensional (2 D); Two dimensional nanosheets; Electrochemistry; Graphene; Graphite; Nanostructures; Supercapacitor; Tungsten vanadate